Development and evaluation of in situ gel of pregabalin - Madan, Jyotsana R; Adokar, Bhushan R; Dua, Kamal (International Journal of Pharmaceutical Investigation)
Aim and Background: Pregabalin (PRG), an analog of gamma-aminobutyric acid, reduces the release of many neurotransmitters, including glutamate, and noradrenaline. It is used for the treatment of epilepsy; simple and complex partial convulsion. The present research work aims to ensure a high drug absorption by retarding the advancement of PRG formulation through the gastrointestinal tract. The work aims to design a controlled release PRG formulation which is administered as liquid and further gels in the stomach and floats in gastric juice. Materials and Methods: In situ gelling formulations were prepared using sodium alginate, calcium chloride, sodium citrate, hydroxypropyl methylcellulose (HPMC) K100M, and sodium bicarbonate. The prepared formulations were evaluated for solution viscosity, drug content, in vitro gelling studies, gel strength, and in vitro drug release. The final formulation was optimized using a 32 full factorial design. Results: The formulation containing 2.5% w/v sodium alginate and 0.2% w/v calcium chloride were considered optimum since it showed minimum floating lag time (18 s), optimum viscosity (287.3 cps), and gel strength (4087.17 dyne/cm2). The optimized formulation follows Korsmeyer-Peppas kinetic model with n value 0.3767 representing Fickian diffusion mechanism of drug release. Conclusion: Floating in situ gelling system of PRG can be formulated using sodium alginate as a gelling polymer and calcium chloride as a complexing agent to control the drug release for about 12 h for the treatment of epilepsy.
Keywords: Floating drug delivery; in situ gel; pregabalin